Investments and the NIMBY Syndrome in Waste Management – Analysis Based on the Example of the Małopolskie Voivodeship - Kultys-Grabowska, Aleksandra (Inwestycje i syndrom NIMBY w gospodarce odpadami – analiza na przykładzie województwa małopolskiego, 2022)
The aim of the article was to determine to what extent the NIMBY syndrome may hinder the implementation of investments in waste management in the Małopolskie Voivodeship. The background of the analysis was the premise of the European Green Deal, including the need to implement a circular economy. The article consists of an analysis of investment outlays in waste management in Małopolska, defining the NIMBY syndrome, and an analysis of the results of a survey conducted among respondents in the region. It was found that potential investments in waste management should not encounter financing problems. In terms of public resistance, social protests can be triggered by investments in the form of landfills and waste incineration plants. Investments related to waste recycling raised less public objection. Social opposition also grew when the more pejorative name of the facility was used.
Financial Sciences. Nauki o Finansach, 2022, vol. 27, no. 1, s. 69-81
Keywords: NIMBY syndrome; waste management; investments; circular economy; European Green Deal; syndrom NIMBY; gospodarka odpadami; inwestycje; gospodarka obiegu okrężnego; Europejski Zielony Ład